2020
DOI: 10.1507/endocrj.ej19-0444
|View full text |Cite
|
Sign up to set email alerts
|

GnRH(1-5), a metabolite of gonadotropin-releasing hormone, enhances luteinizing hormone release <i>via</i> activation of kisspeptin neurons in female rats

Abstract: Accumulating evidence suggests that kisspeptin neurons in the arcuate nucleus (ARC), which coexpress neurokinin B and dynorphin, are involved in gonadotropin-releasing hormone (GnRH)/luteinizing hormone (LH) pulse generation, while the anteroventral periventricular nucleus (AVPV) kisspeptin neurons are responsible for GnRH/LH surge generation. The present study aims to examine whether GnRH(1-5), a GnRH metabolite, regulates LH release via kisspeptin neurons. GnRH(1-5) was intracerebroventricularly injected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
(64 reference statements)
1
16
0
Order By: Relevance
“…Animals then immediately received subcutaneous Silastic implants (internal diameter: 1.57 mm; outer diameter: 3.18 mm; 3 mm in length; Dow Corning, Midland, MI, USA) that were filled with estradiol-17β (E 2 ; Sigma-Aldrich, St Louis, MO, USA) dissolved in peanut oil at 10 µg/ml. The E 2 implant was chosen based on our previous studies [42][43][44] to visualize Kiss1 gene expression in both the AVPV and ARC: the size and dose were adjusted according to the animal body weight. Ovaries were weighed and stored at -80 o C until analysis for Kiss1 and Cre mRNA expression.…”
Section: Ovary Collection and Estradiol Treatmentmentioning
confidence: 99%
“…Animals then immediately received subcutaneous Silastic implants (internal diameter: 1.57 mm; outer diameter: 3.18 mm; 3 mm in length; Dow Corning, Midland, MI, USA) that were filled with estradiol-17β (E 2 ; Sigma-Aldrich, St Louis, MO, USA) dissolved in peanut oil at 10 µg/ml. The E 2 implant was chosen based on our previous studies [42][43][44] to visualize Kiss1 gene expression in both the AVPV and ARC: the size and dose were adjusted according to the animal body weight. Ovaries were weighed and stored at -80 o C until analysis for Kiss1 and Cre mRNA expression.…”
Section: Ovary Collection and Estradiol Treatmentmentioning
confidence: 99%
“…Several studies revealed a strong expression in the CNS in different species (zebrafish, rodents and humans), suggesting its function has been conserved during evolution. In particular, GPR101 is highly expressed in the amygdala and hypothalamus, especially the ARC, and in the nucleus accumbens (NAc) (Bates et al 2006, Nilaweera et al 2007, Regard et al 2008, GTEx Consortium 2013, Ronnekleiv et al 2014, Trivellin et al 2014, Ehrlich et al 2018, LaRese et al 2019, Ieda et al 2020. Other human tissues showing moderate mRNA expression are fat, optic nerve and lymphocytes (Trivellin et al 2016a).…”
Section: Tissue Expressionmentioning
confidence: 99%
“…Starvation was also found to increase Gpr101 expression in the posterior hypothalamus, while ob/ob obese mice showed decreased expression. Within the ARC, Gpr101 is expressed in about 50% of the neurons expressing the anorexigenic peptide proopiomelanocortin (POMC) (Nilaweera et al 2007) and in glutamatergic neurons (Ieda et al 2020), while thyrotropin-releasing hormone (TRH) positive neurons expressed Gpr101 in the lateral hypothalamus (Mickelsen et al 2019). All these brain regions are implicated in various aspects of feeding and reward (Uribe-Cerda et al 2018).…”
Section: Tissue Expressionmentioning
confidence: 99%
See 2 more Smart Citations